Case report: Purulent transformation of granulocytic sarcoma. Issue 8 (February 2018) - Collinge, Elodie; Tigaud, Isabelle; Balme, Brigitte; Gerland, Luc-Marie; Sujobert, Pierre; Carlioz, Violette; Salles, Gilles; Thomas, Xavier; Paubelle, Etienne
Abstract: Rationale: Acute promyelocytic leukemia (APL) is a curable subtype of acute myeloid leukemia. APL is currently treated with combination of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) resulting in the induction of apoptosis and differentiation of the leukemic cells. Differentiation syndrome (so-called ATRA syndrome) is the main life-threatening complication of induction therapy with these differentiating agents. Patient concerns: Herein, we report the case of a 49-year-old woman diagnosed with APL with, concomitantly, a bulky cutaneous lesion of 10 cm diameter with a red-to-purple background and a necrotic center, localized on her abdomen. Diagnoses: After 10 days of treatment, the cutaneous lesion became purulent. Fluorescence in situ hybridization (FISH) analysis performed on this pus confirmed the presence of malignant features in the involved granulocytes proving their origin from the differentiation of leukemic APL cells, as all the analyzed nuclei showed 2 promyelocytic leukemia (PML)–retinoic acid receptor-a (RARA) fusions signals. Intervention: The association by ATRA and ATO was continued. Outcome: Eventually, the evolution was favorable with healing in three weeks. Lessons: This case report therefore highlights the differentiation phenomenon of promyelocytic blasts within promyelocytic sarcoma with the ATRA–ATO combination and the efficacy of this drug association in resolving both the malignant sarcoma and a secondary local infection.